Determinants of Customer Satisfaction in Context of Retail Malls: Empirical Evidence from India - Yousaf, Anish; Arora, Neelika; Gupta, Anil (Indian Journal of Marketing, 2015)
The Indian consumer market has seen a significant growth in the number of modern-day shopping centers, popularly known as ’malls’. This industry is changing at a very fast pace, and global competition has brought new demands such as the provision for additional facilities and flexibility within malls. The uncertain business environment has brought into question traditional notions of managing retail infrastructure and puts pressure on mall administrations to attract more footfalls in their malls to attract global/national retailers. Highlighting the importance of customer satisfaction in context of shopping malls, the current study explored the factors (using factor analysis), which could impact customer satisfaction. Higher satisfaction scores across the items of atmosphere dimensions suggested that atmosphere was an important dimension which customers used as a cue to evaluate any shopping mall. Furthermore, the image of the mall, number of events organized, and the promotional schemes&discounts offered within the mall premises were also evaluated by the consumers. Customers visiting the malls expect sales promotion schemes and discounts to be offered to them. The managements/managers of malls should also organize special events within the mall premises to attract customers’ attention.